Modeling demand of telecommunication technologies in Malaysia - Mahat, Nor Idayu; Ang, Chooi Leng; Engku Abu Bakar, Engku Muhammad Nazri; Ramli, Razamin; Abd Karim, Mohd Zaini; Pang, Lih Mey; Alias, Mohd Yusof (2010)
Forecasting the demand of telecommunication technologies is a crucial task for authorised spectrum management and service providers due to fast development and changes of these technologies. A good forecasting model is helpful to portray Malaysian's acceptance towards communication facilities. Thus, this information can be fully utilised to structure some strategies to ensure Malaysians are benefited from the technologies no matter where they are. This paper reports on a study aimed to determine the telecommunication technologies demand among Malaysians and attempts to model such demand mathematically. Four telecommunication technologies investigated are direct exchange line, cellular phone, internet dial-up and internet broadband. Some statistical models studied include simple linear regression, quadratic regression,growth curve model and Holt's trend corrected exponential smoothing model. This study discovers that different telecommunication technologies indicate different patterns of demand with different acceleration. the penetration rate of cellular phone is suitable to be modelled by the Holt's method and the remaining technologies are suggested to perform quadratic behavior.